The association between physical activity and lung function in adolescents: a cross-sectional NHANES study - Chen, Xiaoyuan; Ma, Jinhai; Dong, Linghua; Chen, Yan; Chen, Keke (Frontiers in Medicine, 2025)
BackgroundThis study investigates the relationship between physical activity (PA) and lung function in adolescents using data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2012. While physical activity is known to improve respiratory health, its impact on specific lung function parameters in adolescents, particularly across different activity intensities, remains underexplored.MethodsWe analyzed the effects of varying intensities of PA on lung function parameters—specifically Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 s (FEV₁), and Forced Expiratory Flow (FEF)—in a sample of 896 adolescents aged 12–19 years. Linear regression analyses were employed to examine the relationship between PA duration and lung function, adjusting for potential confounders. The sample was stratified by intensity of PA (low, moderate, and high) to assess differential impacts on lung function.ResultsThe analysis revealed significant improvements in lung function with increased PA duration, with high-intensity PA showing the most pronounced effects. Specifically, high-intensity PA was associated with a 2.0 (95% CI: 0.43, 3.5) increase in FVC and a 2.0 (95% CI: 0.74, 3.4) increase in FEV₁ per unit increase in activity. Moderate-intensity PA also demonstrated significant improvements in lung function, though to a lesser extent. Stratified analyses identified significant associations within certain racial subgroups, with Mexican American and Other Hispanic adolescents more likely to maintain normal lung function.ConclusionThese findings highlight the importance of regular physical activity, particularly high-intensity exercise, in enhancing lung function during adolescence. The results emphasize the need for targeted public health interventions to encourage PA, especially in racially diverse populations. Further longitudinal studies are needed to evaluate the long-term effects of PA on lung health and to establish causal relationships.